Hubungan gaya pembelajaran dengan pencapaian Sains - Che Azizon, Che Yusof (2009)
The study examines the relations between students' learning styles and achievement in Science subject. The sample of the research consisted of 200 respondents which 91 respondents belong to male student while the others 109 belongings to female students. The study employed a set of questionnaire measuring on students' different learning styles using four point scales. The three categories of learning styles by Dunn and Dunn Models (1978) are Emotional (motivation, persistence, responsibility and structure), Sociological (self, pair, peers, pair and adult) and Physical (perceptual, intake, time and mobility). Its shows female students more prefer on motivation, persistence, responsible rather than male students. In studies Sciences, female students also prefer to pair and group studies. The research data is analyzed based ANOVA and Pearson correlation analysis. The results obtained shows that female respondents prefer to apply Emotional and Sociological category as a learning style in Science subject. The finding shows that female students have high motivation, high persistence, responsible and like clear structure instruction. Female student are prefer to study in pair and group compared to male students in science subject. The results obtained shows that the learning styles is different significantly with the respondents' gender. Results also show that the different learning styles by students have no correlation with students' academic achievement. This research will helped school administration, student, parent and Ministry of Education to improved suitable teaching styles with learning styles to produce excellent students